Synthesis of Gold Nanobipyramids by Seed-mediated Method and Santibacterial Activities - Ngo, Thanh Vo Ke; Huynh, Phat Trong; Nguyen, Anh Thi Kim; Nguyen, Giang Dang; Lam, Vinh Quang (Communications in Physics, 2018)
Metallic nanoparticles as antibacterial agents have been studied for several years. The most used antibacterial nanoparticles are silver nanoparticles. The mechanisms and antibacterial properties of silver nanoparticles are well known, but the effects of gold nanoparticles, especially gold Nano bipyramids, are not considered. In this research, we synthesized gold nanobipyramids (NBPs) by seed mediated method using surfactant cetyltrimethylammonium bromide (CTAB). After preparing, gold nanobipyramids is removed CTAB and modified the surface using polyethylene glycol, polyvinyl alcohol and chitosan as the stabilizers. Besides, antibacterial effects of gold nanobipyramids on both Escherichia coli (Gram negative) and Staphylococcus aureus (Gram positive) are investigated in this paper. The results show that gold nanobipyramids have good antibacterial activities even at low concentration. The optimal concentration of stabilizers and gold nanobipyramids in antibacterial activities are also studied in this paper.